Faktor-Faktor Penyebab Anak Nelayan Putus Sekolah di Kelurahan Pasia Nan Tigo Kecamatan Koto Tangah Kota Padang - Vanessa Vanessa; Fitri Eriyanti (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
This article describe the factors that cause fishermen children who drop out of school in Pasia Nan Tigo Subdistrict Koto Tangah Padang City. In this study, it was intended to find out what are the factors taht cause fishermen’s children to drop out of school in Pasia Nan TigoVillage. This Research uses qualitative approach, and research type using descriptive method. Data collection techniques in this study through interviews, observations and documentation studies, instruments in this study are interview guidelines that have been prepared, as well as mobile phones to collect data in research. In the research data reduction can be drawn conclusions from the data taht has been obtained. The results showed that the factors that cause fishermen to drop out of school in Pasia Nan Tigo Village are the economic factors of parents, the environment,parents’ awareness about the meaning of education, workfactors and interest an motivation factors.